2018
DOI: 10.1167/18.11.19
|View full text |Cite
|
Sign up to set email alerts
|

The spectral identity of foveal cones is preserved in hue perception

Abstract: Organisms are faced with the challenge of making inferences about the physical world from incomplete incoming sensory information. One strategy to combat ambiguity in this process is to combine new information with prior experiences. We investigated the strategy of combining these information sources in color vision. Single cones in human subjects were stimulated and the associated percepts were recorded. Subjects rated each flash for brightness, hue, and saturation. Brightness ratings were proportional to sti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
(152 reference statements)
1
14
0
Order By: Relevance
“…The responses are highly consistent and reflect activity in the midget RGCs with single cone centers (Schmidt et al, 2019). Consistent with parallel processing of hue and spatial information by separate types of midget RGCs, stimulation of most L/M-cones in the central retina results in percepts of white, with only a small subset eliciting color percepts (Figure 3B; Sabesan et al, 2016; Schmidt et al, 2018a, b). Further, the homogeneity of the surrounding cone type had no effect on which cones were associated with a perceived color, arguing against the idea that midget RGCs with strong L vs. M opponency serve hue perception.…”
Section: Parallel Processing Modelssupporting
confidence: 54%
“…The responses are highly consistent and reflect activity in the midget RGCs with single cone centers (Schmidt et al, 2019). Consistent with parallel processing of hue and spatial information by separate types of midget RGCs, stimulation of most L/M-cones in the central retina results in percepts of white, with only a small subset eliciting color percepts (Figure 3B; Sabesan et al, 2016; Schmidt et al, 2018a, b). Further, the homogeneity of the surrounding cone type had no effect on which cones were associated with a perceived color, arguing against the idea that midget RGCs with strong L vs. M opponency serve hue perception.…”
Section: Parallel Processing Modelssupporting
confidence: 54%
“…However, if output from a subset of cones was reserved exclusively for chromatic vision, this would degrade achromatic acuity and, as mentioned above, acuity at the foveal center closely follows the Nyquist limit predicted from cone-to-cone spacing (391). An alternate idea is that the brain might learn a map of the cone mosaic through experience (26,396). While the likelihood of reporting green or red following single cone stimulation was not significantly enhanced in cones that were immediately surrounded by cones of a different spectral sensitivity (393), the threshold for single cone detection of a colored light stimulus was elevated by use of an adapting light of the opposite color when the cone was surrounded by cones of the opposite spectral sensitivity (453).…”
Section: Midget L Versus M "Red-green" Opponent Circuitmentioning
confidence: 92%
“…Does it matter if this is achieved through increasing the stimulus size, or by allowing a small stimulus to move across the retina? And finally, while previous research has shown that varying the intensity of single-cone stimuli does not affect hue perception (Schmidt et al, 2018), does it have an effect for larger stimuli?…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have examined the repeatability of hue judgments for stimuli delivered to individual cones and pairs of cones (Sabesan et al, 2016; Schmidt et al, 2018; Schmidt et al, 2019). In the current study, a different group of 6-7 target locations centered on cones were chosen on each session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation